Assessment of Awareness, Knowledge, and Attitude of Dentistry Students in Kermanshah University of Medical Sciences Regarding Evidence-Based Dentistry (EBD) - Atefeh Khavid (International Journal of Scientific Research in Dental and Medical Sciences, 2019)
Background and aim: Evidence-Based Dentistry (EBD) in clinical education for students and based on the specific conditions governing over any university including difference in rate of focusing on this area of education in various fields and how much Kermanshah Faculty of Dentistry has dealt with this field. The aim of this study was, Assessment Thus, awareness, knowledge, and attitude of dentistry students have been examined about Evidence-Based Dentistry (EBD) in Kermanshah University of Medical Sciences. Materials and methods: This study is a cross-sectional (descriptive- analytical) research that has been carried out on junior and senior students of dentistry faculty of Kermanshah University of Medical Sciences. Finally, 82 subjects were included in this study. Their awareness, knowledge and attitude were examined about EBD using a standardized questionnaire. Data entered SPSS.v24 software after completion of information forms and were finally analyzed. Results: The scores of students in variables of awareness, attitude abs self- assessed knowledge were 23.22±3.57 EBD (maximum=50), 48.04±3.35 EBD (maximum=60) and 17.62±3.81 EBD (maximum=45) respectively. The mean score was higher among female students than males and this difference was statistically significant (P<0.05). The mean score of self-assessed attitude had a positive significant correlation with academic year (P<0.05). Similarly, the average of students showed a significant relationship with their self-assessed awareness and knowledge regarding EBD (P<0.01). Conclusion: students’ relatively well attitude toward EBD, but they did not acquire adequate awareness and knowledge about Evidence-Based Dentistry (EBD).